IMPLEMENTASI MODEL PEMBELAJARAN RECIPROCAL LEARNING BERBANTUAN SOAL OPEN ENDED UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA - Lena Rosdiana Pangaribuan; Simon Maruli Panjaitan; Lolyta Damora Simbolon; Halmaliana Lorensia br. Kembaren (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
One of the educational problems that has become a priority is the quality of education. From the various problems in the field, the effort we can make is to develop student-centered learning. Based on observations conducted at SMA Negeri 15 Medan, many teachers tend to use an expository model and assign individual tasks rather than group work in the classroom learning process. Most of the homework completed by students tends to have the same answers. Data obtained from the mathematics teacher indicates that student learning outcomes are still relatively low, as seen from the results of the odd semester final exam 2023/2024, where 58% of students scored below 70. This is caused by a lack of understanding and mastery of the material, so the learning outcomes achieved are not yet satisfactory. Therefore, teachers must choose a learning implementation that can make the material meaningful to students. One alternative for selecting a learning strategy is reciprocal learning assisted by open-ended questions. This study aims to determine whether the use of the Reciprocal Learning strategy can improve students' mathematical problem-solving abilities. This study is a Classroom Action Research using Reciprocal Learning with four main activities, namely questioning, clarifying, predicting, and summarizing/reviewing, with stages including: planning, implementation, monitoring, and reflection carried out in several cycles. This research was conducted at SMA Negeri 15 Medan in class XI IPA. Data collection techniques were through observation, questionnaires, interviews, and tests.